Sexual behaviour and reproductive performance of the endangered European eel Anguilla anguilla (Linnaeus, 1758) based on direct observations and paternity assignment in semi-natural conditions - Ilaria Guarniero (Aquaculture Reports, 2020)
European eel Anguilla anguilla is among the highly valued species for aquaculture. Since its peculiar biology, it is not yet possible to complete the whole life cycle in artificial conditions and its supply depends entirely on wild catches. In the last 50 years this species has suffered a population reduction of 99 % mainly due to overfishing. In a conservation perspective, it is of fundamental importance to improve the aquaculture production of European eel, to avoid the extinction of this species and preserve its residual genetic variability, allowing at the same time the fulfilling of costumers request without increasing its harvesting pressure.In this study we aimed to deepen the knowledge about the mechanisms at the basis of reproduction of the European eel in semi-natural conditions, through direct observation of spawning behaviour and through the paternity assignment using microsatellite markers. The systematic and prolonged observation of the reproductive behaviour of European eel and the contextual parentage analyses we carried out for the very first time in this species on 39 adults and 432 F1 randomly collected. We contributed to unravel the sexual behaviour of this species in the most common artificial reproduction conditions (polyandry), and define the precise courtship sequence until the release of gametes, and the male-male hierarchy in courtship. We characterized for the first time three main types of male: dominant (the first who starts the courtship, and the one with the majority of F1 assigned), subordinate (which starts the courtship only in a second time and with a minor percentage of F1 ascribed) and ineffective (which sometime appears totally disinterested to courtship and has few F1 or none).The evidences here produced represent an important attempt for developing good reproduction practices of the critically endangered European eel, providing a good starting point for its future aquaculture production. Keywords: Anguilla anguilla, Aquaculture, Artificial breeding, Kinship analysis, Parentage assignment